2012
DOI: 10.1063/1.4770317
|View full text |Cite
|
Sign up to set email alerts
|

Method for determining the radiative efficiency of GaInN quantum wells based on the width of efficiency-versus-carrier-concentration curve

Abstract: We report a method to determine the radiative efficiency (RE) of a semiconductor by using room-temperature excitation-dependent photoluminescence measurements. Using the ABC model for describing the recombination of carriers, we show that the theoretical width of the RE-versus-carrierconcentration (n) curve is related to the peak RE. Since the normalized external quantum efficiency, EQE normalized , is proportional to the RE, and the square root of the light-output power, ffiffiffiffiffiffiffiffiffi LOP p , is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Attempts to develop a practical technique for the IQE evaluation, which would not implement any computational stage, has resulted in proposal of two approximate versions of the approach [18]. One of them suggested to measure the width of the dome-like  e ( I ) dependence at a certain height [20], whereas another one implied to measure the curvature of the dependence at the maximum point [21], which enabled estimation of the peak IQE. Despite the attractive simplicity of the approaches, they were not yet widely employed in practice.…”
mentioning
confidence: 99%
“…Attempts to develop a practical technique for the IQE evaluation, which would not implement any computational stage, has resulted in proposal of two approximate versions of the approach [18]. One of them suggested to measure the width of the dome-like  e ( I ) dependence at a certain height [20], whereas another one implied to measure the curvature of the dependence at the maximum point [21], which enabled estimation of the peak IQE. Despite the attractive simplicity of the approaches, they were not yet widely employed in practice.…”
mentioning
confidence: 99%
“…They are the single QW pn-junction LED (“SQW LED”), the five multiple QW LED (“5QW LED”), and the n-type GaN/SQW/n-type GaN sample (“n/SQW/n sample”). A detailed description of the SQW LED and the n/SQW/n sample can be found in a previous report . Before stating our main experiment and results, we note that the samples used in this study have an adequate quality for investigating the typical phenomenon of PL and EL droop.…”
Section: Methodsmentioning
confidence: 99%
“…[6][7][8]11,[14][15][16] Furthermore, several previous studies have shown that the excitation density at the onset of the PL droop coincides with that at the onset of the EL droop, and thus the EL and PL droop is likely caused by the same non-radiative recombination inside the active region. 2,9 However, there are also reports that found little or no efficiency droop at optical excitation densities of about kW/cm 2 in PL measurements.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To calculate the IQE, a generally accepted ABC model is use [24,[26][27][28]. The carrier recombination can occur either as radiative recombination, during which light is generated or as the non-radiative recombination, without output light.…”
Section: Wall-plug Efficiency (Wpe)mentioning
confidence: 99%